Влияние слоя поликристаллического кремния на механизмы токопереноса в контактах «металл — p-кремний» - Smyntyna, V. A.; Kulinich, О. А.; Yatsunskii, I. R.; Sviridova, O. V.; Marchuk, I. A. (PE "Politekhperiodika", Book and Journal Publishers, 2011)
Based on the results of investigations of charge transport in the "metal — p-Si" contacts with different thickness of polycrystalline p-Si layer the mechanisms of charge transport through such structures are shown. It is established that with increasing thickness of the layer of polycrystalline p-Si current transport mechanism changes from a double injection into the drift-diffusion. This change is due to an increase in the drift current component in the space charge zone of "metal — p-Si" contact, which arises as a result of increased surface density of scattering barriers, which are localized at the boundaries of neighboring silicon polycrystals.